(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
New derivatives of 2,5-dihydro-2-oxofurans have been obtained by interaction of 2,5-dihydro-4-methyl-5,5-dimethyl(pentamethylen)-2-oxofuran-3-carboxamides with chloranhydrides of acetic, propionic, butyric acids and also with 2,5-dihydro-3-ethoxycarbonyl-4-brommethyl-5,5-dimethyl-2-oxofuran.